2003
DOI: 10.1385/ct:3:2:101
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-Degrading and Pro-Inflammatory Changes in Human Vascular Endothelial Cells Exposed to Cigarette Smoke Condensate

Abstract: Cigarette smoking has been associated with an increase in the severity and prevalence of atherosclerosis in the abdominal aorta. To begin our investigation of this finding, we used an integrated approach combining gene expression profiling, protein analysis, cytokine measurements, and cytotoxicity determinations to examine molecular responses of cultured human aortic and coronary endothelial cells exposed to cigarette smoke condensate (CSC) and nicotine. Exposure of endothelial cells to CSC (30 and 60 microg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 32 publications
6
61
0
Order By: Relevance
“…Exposure of endothelial cells to cigarette smoke condensate induces expression of MMP-1, MMP-8, and MMP-9. 107 Carotid endarterectomy specimens from cigarette smokers have higher MMP-12 and lower TIMP-1 expression than those from nonsmokers, and this is associated with decreased elastin content. 108 Variation in the stromeolysin-1 gene and smoking status demonstrated synergy in conferring risk for myocardial infarction.…”
Section: Smoking and Regulation Of Matrix Metalloproteinase Activitymentioning
confidence: 96%
“…Exposure of endothelial cells to cigarette smoke condensate induces expression of MMP-1, MMP-8, and MMP-9. 107 Carotid endarterectomy specimens from cigarette smokers have higher MMP-12 and lower TIMP-1 expression than those from nonsmokers, and this is associated with decreased elastin content. 108 Variation in the stromeolysin-1 gene and smoking status demonstrated synergy in conferring risk for myocardial infarction.…”
Section: Smoking and Regulation Of Matrix Metalloproteinase Activitymentioning
confidence: 96%
“…Smoking also increases vascular smooth muscle cell proliferation and migration through activation of the platelet-derived growth factor-protein kinase C signalling cascade and alterations in the extracellular matrix and tissue remodelling through increased expression of matrix metalloproteinases (MMP-1/8/9) 199,[209][210][211] . Overall, smoking contributes to endothelial damage and dysfunction, with a shift towards a pro-oxidative and pro-inflammatory state that accelerates atherogenesis and increases the risk of atherosclerotic cardiovascular events 199 .…”
mentioning
confidence: 99%
“…Studies have also shown the increased expression of MMP9 along with other MMPs in endothelial cells exposed to cigarette smoke condensate [27]. Activity of MMP is regulated at the levels of gene transcription, proenzyme activation and endogenous inhibitors of MMPs.…”
Section: Resultsmentioning
confidence: 99%